Antidiuretic Effects of the Endothelin Receptor Antagonist Avosentan - Baltatu, Ovidiu C.; Iliescu, Radu; Zaugg, Christian; Reckelhoff, Jane F.; Louie, Pat; Schumacher, Christoph; Campos, Luciana A. (Frontiers in Physiology, 2012)
Several clinical studies have investigated the potential benefits of endothelin receptor antagonism in chronic pathologies such as diabetic kidney disease. However, fluid retention and edema have been identified as major side effects of endothelin receptor antagonists. In the present study we hypothesized that avosentan which was described as a predominant ETA receptor antagonist would produce fluid retention at high concentrations where non-specific blockade of ETB receptors may occur. Incremental doses of the predominant ETA receptor antagonist SPP301 (0.003; 0.03; 3 mg/kg) were administered intravenously to anesthetized Sprague-Dawley rats undergoing saline diuresis. Diuresis, glomerular filtration rate and blood pressure were monitored. SPP301 decreased urine output (5.6; 34.8; 58.8% decrease from vehicle) and fractional excretion of water (5.7; 31.7; 56.4% decrease from vehicle) in a concentration-dependent manner. Glomerular filtration rate was unchanged while blood pressure was reduced by 10 mmHg only by the highest dose of SPP301. Administration of the ETB selective receptor antagonist BQ-788 (3 mg/kg) following SPP301 3 mg/kg did not further decrease urine output or water excretion and was without effect on glomerular filtration rate. These data indicate that increasing concentrations of SPP301 may also block ETB receptors and cause antidiuresis. This effect could explain why fluid retention and edema occur during treatment with predominant ETA receptor blockers.